Appraisal Arbitrage and the Future of Public Company M&A - Charles R. Korsmo; Minor Myers (Washington University Law Review, 2015)
In this Article, we demonstrate that the stockholder’s appraisal remedy—long-dismissed in corporate law scholarship as useless or worse—is in the middle of a renaissance in public company mergers. We argue that this surge in appraisal activity promises to benefit public shareholders in circumstances where they are most vulnerable. We first show a sea change in the use of appraisal in Delaware. Relying on our hand-collected data, we document sharp recent increases in the incidence of appraisal petitions, in the size of the petitioners’ holdings, and in the sophistication of the petitioners targeting public deals. These litigants appear to invest in target company stock after the announcement of the merger and with the intention of pursuing appraisal. In short, this is appraisal arbitrage. There is every reason to believe that appraisal now stands as the most potent legal challenge to opportunistic mergers. We also present evidence showing that these appraisal petitions bear strong markers of litigation merit—they are, in other words, targeting the right deals. Nevertheless, defense lawyers have recently suggested that appraisal arbitrage constitutes some sort of “abuse” of the remedy and ought to be stopped. This nascent argument has matters precisely backwards. This new world of appraisal should be welcomed and indeed encouraged. Our analysis reveals that appraisal arbitrage focuses private enforcement resources on the transactions that are most likely to deserve scrutiny, and the benefits of this kind of appraisal accrue to minority shareholders even when they do not themselves seek appraisal. In this way, the threat of appraisal helps to minimize agency costs in the takeover setting, thereby decreasing the ex ante cost of raising equity capital and improving allocative efficiency in public company mergers and acquisitions. We offer some modest reforms designed to enhance the operation of the appraisal remedy in Delaware.
Keywords: Appraisal remedy; Public company mergers; Corporate Law; Mergers and Acquisitions; Appraisal; Appraisal petition